Improving Students' Ability to Identify Insulators and Conductors Through Demonstration and Experimentation in Buluh 1 Elementary School - Faradila, Nadya; Fajrin, Weny; Saputra, Yoga (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
This research aims to improve students' ability to identify insulators and conductors through the application of demonstration and experimental methods in science learning. In this learning approach, students will be actively involved in direct observation, experiments, and analysis of results to understand the concept of the properties of insulators and conductors. The implementation of this research implemented steps including initial planning, implementation and observation, reflection, and revised plans. This research was designed to investigate the effectiveness of this approach in improving students' understanding of the differences between insulators and conductors. Through the use of simple tools such as candles, matches, chopsticks, spoons, paper and cloth. This research was carried out at the Buluh 01 State Elementary School for class VI students, using the Demonstration and Experiment method, it is hoped that students will understand more about science learning. The data collection technique used is observation/observation techniques. This research instrument uses a test questionnaire and observation sheet.The demonstration and experimental methods in this research are said to be effective because they can improve the abilities and learning outcomes of class VI students at SDN Buluh I. It was found that there was a significant increase in the average student scores from cycle I (66) and cycle II (82), and the level of learning completeness increased from cycle I (66.35%) and increased in cycle II by (81.85%). So it can be concluded that the use of this method is very effective in learning insulators and conductors. When conducting this research, researchers are advised to provide sufficient examples, adequate practice, and repeated familiarization.